Containment of Cattle Brucellosis Outbreaks With a Small Dose of Vaccine From Strain 82 - Novitsky , Alexei; Pleshakova, Valentina; Lescheva, Nadezhda; Vlasenko, Vasily (KnE Life Sciences, 2021)
Improving the system of anti-brucellosis measures is the ultimate goal of all studies devoted to the problem of brucellosis. Cattle brucellosis outbreaks in the brucellosisfree regions in the Russian Federation indicate a premature cessation of immunization procedures and the need for their continuation. Meanwhile, there is an urgent problem of developing anti-brucellosis immunity in the adult cattle: the initial vaccination of cattle with a full dose of the vaccine from strain B. abortus 82 is fraught with post-vaccination abortions. In order to solve this problem, in the production conditions of one of the farms where the current epizootic situation for brucellosis required alternative approaches for containment of a brucellosis outbreak, a small dose of the vaccine was tested on the cattle without specific immunity. This resulted in immunogenicity, loss of abortogenicity and the presence of provocative properties of the vaccine in small doses. This allowed the detection of antibodies in animals with a hidden infection in the early stages after vaccination. Serological methods (AT, RBT and IDR with O-polysaccharide antigen), which are generally accepted in veterinary practice, were used as diagnostic tests. The reimmunization of the cows with a small dose of the vaccine from strain 82 allowed diagnostic tests to be carried out earlier after vaccination than after the use of a full dose of the vaccine, which made it possible to diagnose brucellosis in a short period of time after vaccination. The provocation of immunological reactions in latently sick animals after the vaccination with small doses, and the isolation of those who responded under the condition of supported immunity made it possible to achieve the recovery of farm animals in a short period of time, which was proved by negative indicators of the immunodiffusion reaction with O-polysaccharide antigen. Keywords: brucellosis, small doses of the vaccine, abortogenicity, immunity